Mechanical Circulatory Support Device Utilization and Heart Transplant Waitlist Outcomes in Patients With Restrictive and Hypertrophic Cardiomyopathy. (March 2018) - Sridharan, Lakshmi; Wayda, Brian; Truby, Lauren K.; Latif, Farhana; Restaino, Susan; Takeda, Koji; Takayama, Hiroo; Naka, Yoshifumi; Colombo, Paolo C.; Maurer, Mathew; Farr, Maryjane A.; Topkara, Veli K.
Abstract : Background: Patients with restrictive cardiomyopathy (RCM) and hypertrophic cardiomyopathy (HCM) generally are considered poor candidates for mechanical circulatory support devices (MCSDs) and often not able to be bridged mechanically to heart transplantation. This study characterized MCSD utilization and transplant waitlist outcomes in patients with RCM/HCM under the current allocation system and discusses changes in the era of the new donor allocation system. Methods and Results: Patients waitlisted from 2006 to 2016 in the United Network for Organ Sharing registry were stratified by RCM/HCM versus other diagnoses. MCSD utilization and waitlist duration were analyzed by propensity score models. Waitlist outcomes were assessed by cumulative incidence functions with competing events. Predictors of waitlist mortality or delisting for worsening status in patients with RCM/HCM were identified by proportional hazards model. Of 30 608 patients on the waitlist, 5.1% had RCM/HCM. Patients with RCM/HCM had 31 fewer waitlist days ( P <0.01) and were ≈26% less likely to receive MCSD ( P <0.01). Cumulative incidence of waitlist mortality was similar between cohorts; however, patients with RCM/HCM had higher incidence of heart transplantation. Predictors of waitlist mortality or delisting for worsening status in patients with RCM/HCM without MCSD support included estimated glomerular filtration rate <60 mL/min per 1.73 m 2, pulmonary capillary wedge pressure >20 mm Hg, inotrope use, and subjective frailty. Conclusions: Patients with RCM/HCM are less likely to receive MCSD but have similar waitlist mortality and slightly higher incidence of transplantation compared with other patients. The United Network for Organ Sharing RCM/HCM risk model can help identify patients who are at high risk for clinical deterioration and in need of expedited heart transplantation. Abstract : Supplemental Digital Content is available in the text.